2020
DOI: 10.4103/nmj.nmj_200_20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on thyroid autoimmunity among subjects of autoimmune thyroid disease in a coastal province of India: A randomized open-label trial

Abstract: Objective: Hashimoto's thyroiditis (HT) is a variant of autoimmune thyroid disorders (AITD) which has been associated with vitamin D (vit-D) deficiency. However, whether vit-D supplementation is linked to reduction of thyroid autoantibodies and improvement of thyroid function is not well characterized. The present study was planned to evaluate the effect of vit-D supplementation on possible improvement of thyroid autoantibody titer and thyroid hormone profile in patients with AITD subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This comparison study confirm reduced vitamin D level in serum with Hashimoto's thyroiditis cases and show role the level of vitamin D at Hashimoto's thyroiditis development. These results agree with BEHERA, Kishore Kumar, et al 2020 that showed also function and effects of vitamin D in Hashimoto's thyroiditis patients, also demonstrate that vitamin D play as regulation factor in autoimmune disease genes regulation like Hashimoto's thyroiditis disease (10).…”
Section: Resultssupporting
confidence: 91%
“…This comparison study confirm reduced vitamin D level in serum with Hashimoto's thyroiditis cases and show role the level of vitamin D at Hashimoto's thyroiditis development. These results agree with BEHERA, Kishore Kumar, et al 2020 that showed also function and effects of vitamin D in Hashimoto's thyroiditis patients, also demonstrate that vitamin D play as regulation factor in autoimmune disease genes regulation like Hashimoto's thyroiditis disease (10).…”
Section: Resultssupporting
confidence: 91%
“…whereas TSH values demonstrated a statistically significant decrease from 7.23 ± 3.16 to 3.04 ± 2.62 mIU/L (p = 0.01) [35].…”
Section: Implications In Hashimoto's Diseasementioning
confidence: 82%
“…Increases in vitamin D levels were statistically significant: from 15.33 ± 5.71 ng/mL to 41.22 ± 12.24 ng/mL. TPO antibody titers illustrated a statistically significant increase from 746.8 ± 332.2 to 954.1 ± 459.8 IU/mL (p = 0.006), whereas TSH values demonstrated a statistically significant decrease from 7.23 ± 3.16 to 3.04 ± 2.62 mIU/L (p = 0.01) [35].…”
Section: Implications In Hashimoto's Diseasementioning
confidence: 91%
“…D3 level and its effects in HT patients and confirm that vit. D3 act as regulation factor on some genes that regulation autoimmune dis-ease such as HT [10].…”
Section: Discussionmentioning
confidence: 99%